2011
DOI: 10.2147/lra.s23808
|View full text |Cite
|
Sign up to set email alerts
|

The role of regional and neuroaxial anesthesia in patients with systemic sclerosis

Abstract: Systemic sclerosis (SSc), previously known as progressive systemic sclerosis, is a form of scleroderma and a multisystem connective tissue disease which can impact on every aspect of anesthetic care, especially airway management. In this review we outline clinical manifestations and current medical treatment of the disease, and general principles of anesthetizing these patients. We focus on the role of regional anesthesia, including neuroaxial anesthesia, which may serve as a safe alternative to general anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Since 1964, patients in seven out of 21 cases of local and regional anesthesia in individuals with SSc have shown a prolonged sensory block. Six of these seven patients had prolonged peripheral nerve block and only one had a labor epidural block using chloroprocaine [ 13 ]. Thompson and Conklin [ 14 ] reported that T6-S5 anesthesia was maintained for 5 hours and 55 minutes after the injection of 320 mg of chloroprocaine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1964, patients in seven out of 21 cases of local and regional anesthesia in individuals with SSc have shown a prolonged sensory block. Six of these seven patients had prolonged peripheral nerve block and only one had a labor epidural block using chloroprocaine [ 13 ]. Thompson and Conklin [ 14 ] reported that T6-S5 anesthesia was maintained for 5 hours and 55 minutes after the injection of 320 mg of chloroprocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Thompson and Conklin [ 14 ] reported that T6-S5 anesthesia was maintained for 5 hours and 55 minutes after the injection of 320 mg of chloroprocaine. However, a prolonged block has not been reported since 1999, when spinal, epidural, CSE anesthesia, and continuous intrathecal catheter techniques were performed using bupivacaine, ropivacaine, and prilocaine [ 13 ]. Spinal anesthesia was performed in only one parturient patient undergoing a cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Uneventful spinal anesthesia for cesarean section has been reported, but severe hypotension requiring treatment has been noted [ 60 , 77 , 78 ]. Prolonged sensory blockade has been reported and may be related to tissue pH difference reducing the unionized fraction of local anesthetic, or peripheral vascular insufficiency at the regional block location causing reduced clearance [ 75 , 79 , 80 ]. Furthermore, the increasing application of ultrasound guidance has likely reduced the need for high-volume local anesthetic for regional anesthesia, further reducing the risk of prolonged block.…”
Section: Intraoperative Considerationsmentioning
confidence: 99%
“…Given the evidence that invasive ventilation may contribute to SSc-related morbidity, it is reasonable to extrapolate that the appropriate use of regional or neuraxial techniques should be considered in the care of this patient population when possible. Regional and neuraxial techniques have been successfully performed in patients with SSc but may be technically challenging [74][75][76]. Furthermore, autonomic nervous system dysfunction may exacerbate hemodynamic effects of neuraxial anesthesia.…”
Section: Intraoperative Considerationsmentioning
confidence: 99%